SOFTWARE FOR CALCULATING A WATER QUALITY INDICATOR SPECIFIC TO THE AMAZON REGION - Souza, A. M. F. de; Pereira, S. F. P.; Santos, L. P.; Silva, C. S. e; Rocha, R. M.; Sousa, R. M. de; Nogueira, D. P. (International Journal of Research -GRANTHAALAYAH, 2021)
The quality of the water in the Amazon's reservoirs is of fundamental importance for natural ecosystems, biota, and for the region's population. Maintaining the water quality involves long-term monitoring programs established by the requirements of Brazilian legislation. A web interface may facilitate the use of monitoring results routinely, which allows periodic insertion of previously selected water quality parameters results, to finally provide a simple and direct way to evaluate the water quality. The general objective of this study was to develop a software based on a water quality indicator (WQI) system considering chemical, physical-chemical, and biological parameters evaluated in four seasonal periods in Samuel dam. Multivariate analysis was used to select 10 significant variables (oxidation-reduction potential, dissolved oxygen, total dissolved solids, chlorophyll a, phosphate, Ba, Ca, Fe, Na, and Sn). The web software added innovation to the project, enabling to storage of data from analysis of field-collected samples in an organized and safe way in a database, in addition to speeding up the calculation of the WQI, making it possible to classify the water quality more quickly and accurately.